Design module for the industry design and development of a novel gearless Wankel-like mixer–pump: The Lau–Wan mixer. Issue 3 (July 2016) - Lau, MWS; Wan, S; Goh, KL; Leong, J; Lim, A
This paper discusses a case study of a process that provides a holistic design experience by integrating two independent project modules of an undergraduate degree programme. The project proposed by an external party involves the design, manufacture and testing of a scaled prototype for microfluidics applications. The systematic and integrated approach described in the same format as the students' project report resulted in a novel gearless Wankel-like pump that provided visual results that compare well with the external party's numerical studies.